Effectiveness of universal school-based social-emotional learning programs in promoting social-emotional skills, attitudes towards self and others, positive social behaviors, and improving emotional and conduct problems among Japanese children: a meta-analytic review - Takizawa, Yu; Bambling, Matthew; Matsumoto, Yuki; Ishimoto, Yuma; Edirippulige, Sisira (Frontiers in Education, 2023)
The implementation of universal school based Social-Emotional Learning (SEL) programs is increasing in Japanese schools with the aim of enhancing children's social-emotional skills and reducing mental health problems. However, there is a lack of meta-analyses evaluating the effectiveness of these programs in Japan that specifically include studies with control groups and examine program moderators. Conducting such a meta-analysis would be valuable for improving future implementations of SEL programs in Japan. The present meta-analysis analyzed 85 intervention studies with control groups to examine the effectiveness and moderators of universal school based SEL programs for Japanese children aged 5-18 years. The analysis indicates that these programs have a small overall effect (ES = 0.26), as well as small effects in improving socialemotional skills (ES = 0.24), attitude toward the self and others (ES = 0.30), positive social behavior (ES = 0.31), conduct problem (ES = 0.20), and emotional problem (ES = 0.22) at post-intervention among Japanese children. The analysis further revealed that publication type, number of participants, and school level of children moderated the overall effects of universal school based SEL programs, suggesting potential biases in effect sizes reported in peer-reviewed journals published by scientific societies, lower effectiveness for older children, and decreased effectiveness when programs are delivered to larger numbers of children. Future research should explore more effective delivery methods for SEL programs, particularly for older children and larger groups, such as integrating community components and information and communication technology into the programs.1. Are universal school-based SEL programs effective in improving SE skills, attitudes toward the self and others, positive social behavior, conduct problems, emotional problem, and academic performance among Japanese school-aged children at post-intervention?2. Are universal school-based SEL programs effective in improving SE skills, attitudes toward the self and others, positive social behavior, conduct problems, emotional problem, and academic performance among Japanese school-aged children at follow-up?3. Do study characteristics moderate the outcomes of universal school-based SEL programs for Japanese children?32 MethodsA systematic search was conducted on six databases in English (PubMed, PsychINFO, Web of Science, and Dissertation Abstracts) and in Japanese (CiNii Articles and J-STAGE) to obtain a